Social Contract: Sovereign Contracted or Created? - Comparative Analysis Between T. Hobbes and S. Pufendorf - Kalemaj, Eriseld (European Journal of Multidisciplinary Studies, 2017)
This paper has in its focus the notion of 'Sovereign'. The discussion will be conducted within the "School of Natural Law", which we will focus on two representatives; Thomas Hobbes and Samuel Pufendorf. Through a comparative philosophical analysis, we are going to stop on the basics, the genesis of sovereign power. Political philosophy in the context of finding the source of sovereign power is a problem in the landmark of the unsolvable. ” Scool of Natural Law” referring to the natural condition has the solution to this problem. Compare lines will start from this premise, to know after, how the reason goas towards two different concepts of “Social Contract”. Contract which generates sovreigen person, it defines the nature and content of the power of this person. At this discourse, social contract as the core hub of transition, conversion to the state of nature in a civil context is rolling between the political and juridical character. Discussion, which essentially make us know the nature of the relationship between the Sovereign and members of society, sovereign and state, the member of society between each other. In other words, we will see how the political - legal forms of organization, the way of governing is determined by the nature of initial social contract
Keywords: state of nature, social contract, sovereign, civil society